Don Pedro y algunos aspectos interculturales del Vudú - Medrano Marqués, Manuel Mª (Historiografías, 2022)
The magical-religious system of Voodoo in Haiti has had a formation process in the last two centuries crystallized in a synthesis, generally interpreted according to the knowledge on the theme of one author or another, at a specific moment or another of his evolution. The influences of Africa, Europe, and the own developments taken place in Haiti, require analysis to clarify what is the current Voodoo and how it has become what it is. It is a religion organized in each cult center, without superior structures but the temples, which have their own peculiarities, respect a general regulation (règleman) that can be studied as the basis of the entire system. Here we deal with some of these aspects, important to understand a phenomenon that extends beyond the limits of Haiti, and that also permeates Voodoo in Louisiana.